Seismic Structure of Local Crustal Earthquakes beneath the Zipingpu Reservoir of Longmenshan Fault Zone - Haiou Li (International Journal of Geophysics, 2011)
Three-dimensional P wave velocity models under the Zipingpu reservoir in Longmenshan fault zone are obtained with a resolution of 2 km in the horizontal direction and 1 km in depth. We used a total of 8589 P wave arrival times from 1014 local earthquakes recorded by both the Zipingpu reservoir network and temporary stations deployed in the area. The 3-D velocity images at shallow depth show the low-velocity regions have strong correlation with the surface trace of the Zipingpu reservoir. According to the extension of those low-velocity regions, the infiltration depth directly from the Zipingpu reservoir itself is limited to 3.5 km depth, while the infiltration depth downwards along the Beichuan-Yingxiu fault in the study area is about 5.5 km depth. Results show the low-velocity region in the east part of the study area is related to the Proterozoic sedimentary rocks. The Guanxian-Anxian fault is well delineated by obvious velocity contrast and may mark the border between the Tibetan Plateau in the west and the Sichuan basin in the east.